1990
DOI: 10.1016/s0022-5347(17)40082-6
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic Strictures Following Radical Prostatectomy: Risk Factors and Management

Abstract: Stricture of the anastomosis between the bladder neck and membranous urethra after radical prostatectomy can cause significant voiding dysfunction. Of 156 patients undergoing radical prostatectomy for localized prostatic carcinoma 18 had anastomotic stricture for an over-all incidence of 11.5%. The risk factors for anastomotic stricture and the treatment outcome in these patients were analyzed. Excessive intraoperative blood loss, extravasation of urine at the anastomotic site and a prior transurethral prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
133
2
17

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(163 citation statements)
references
References 16 publications
11
133
2
17
Order By: Relevance
“…22 The reported rate of bladder neck contracture after RP ranges from 3 to 11.5%. 10,19,23 The present study assumes a rate of 9% and that transurethral resection of the bladder neck will be performed in one third of these men. The remaining men will be dilated with filiform and followers in the urologist's office an average of 1.7 times and then perform self-catherization for an additional 6 months.…”
Section: Costs Of Complicationsmentioning
confidence: 99%
“…22 The reported rate of bladder neck contracture after RP ranges from 3 to 11.5%. 10,19,23 The present study assumes a rate of 9% and that transurethral resection of the bladder neck will be performed in one third of these men. The remaining men will be dilated with filiform and followers in the urologist's office an average of 1.7 times and then perform self-catherization for an additional 6 months.…”
Section: Costs Of Complicationsmentioning
confidence: 99%
“…Surya et al have demonstrated that the risk factors for anastomotic strictures were excessive blood loss, extravasation of urine at the anastomotic site and a prior transurethral prostatic operation. 19 Therefore, precise anastomosis can prevent the extravasation of urine, followed by preserving strictures of the vesicourethral anastomosis.…”
Section: Tablementioning
confidence: 99%
“…Technical factors postulated to effect BNC rates include: absence of mucosal eversion, poor vesico-urethral apposition, urinary extravasation, excessive narrowing of VUA and ischemia to the bladder neck or membranous urethra (18)(19)(20)(21)(22). Many groups have postulated that excess suture placement may increase the risk of tissue ischemia to the VUA and thus predispose to VUA (23).…”
Section: Introductionmentioning
confidence: 99%